A new species of Proceratophrys Miranda-Ribeiro (Amphibia: Anura: Cycloramphidae) from central Brazil - Martins, Lucas Borges; Giaretta, Ariovaldo Antonio (Zootaxa, 2011)
A new species of the Proceratophrys cristiceps group is described from central Brazil based on adult morphology and advertisement call. Proceratophrys vielliardi sp. nov. is mainly diagnosed by its medium size, lack of tubercular sagittal crests from eyelids to coccyx and a multi-noted advertisement call. This is the second species of Proceratophrys described from central Brazil.